Vagal afferent nerves with the properties of nociceptors - Kollarik, M (2009)
Vagal afferent nerves are essential for optimal neural regulation of visceral organs, but are not often considered important for their defense. However, there are well-defined subsets of vagal afferent nerves that have activation properties indicative of specialization to detect potentially harmful stimuli (nociceptors). This is clearly exemplified by the vagal bronchopulmonary C-fibers that are quiescent in healthy lungs but are readily activated by noxious chemicals and inflammatory molecules. Vagal afferent nerves with similar activation properties have been also identified in the esophagus and probably exist in other visceral tissues. In addition, these putative vagal C-fibers often initiate defensive reflexes, can be sensitized, and have the capacity to induce central sensitization. This set of properties is characteristic of nociceptors in somatic tissues.